Synthesis and evaluation of some new 1,3,4-oxadiazoles bearing thiophene, thiazole, coumarin, pyridine and pyridazine derivatives as antiviral agents - Albratty Mohammed; El-Sharkawy Karam Ahmed; Alhazmi Hassan Ahmed (Acta Pharmaceutica)
In an attempt to produce heterocyclic compounds based on 1,3,4-oxadiazole derivatives with potential antiviral activity, synthesis of compound 1 [2-(5-thioxo-4,5-dihydro-1,3,4-oxadiazol-2-yl)acetonitrile] was performed through the reaction of cyanoacetic acid hydrazide with carbon disulfide in alcoholic potassium hydroxide. Compound 1 has an activating methylene group, so it was directed toward some specific reactions. Thus, aryldiazonium chlorides reacted with compound 1 affording hydrazono derivatives 2a-c. Also, aromatic aldehydes reacted with compound 1 to produce compounds 3a,b. Furthermore, cyclic ketones were subjected to the synthesis of fused thiophene derivatives 4a,bvia reaction with compound 1 in the presence of elemental sulfur. In addition, 1,3,4-oxadiazole derivative 1, when reacted with isothiocyanates, salicylaldehyde or 1,3-dicarbonyl compounds, formed thiazole derivatives 5a,b, coumarin derivative 6 and alkenyl derivatives 7a,b resp. Compound 7b underwent cyclization to afford pyridine derivative 8. Arylhydrazono derivatives 9a,b were produced through the reaction of compound 7a with aryldiazonium chlorides. Products 9a,b underwent cyclization to produce pyridazine derivatives 10a,b. Finally, 1,3,4-oxadiazole derivative 1 was directed toward reaction with hydrazine derivatives, bromoacetophenone and ethylchloroacetate affording compounds 11a,b, 12 and 13, resp. Fused thiophene derivatives 14a,b were produced via reaction of compounds 4a,b with a mixture of malononitrile and ethylorthoformate. Antiviral activity of the synthesized products showed that 5-(4-amino-3-ethyl-2-thioxo-2,3-dihydrothiazol-5-yl)-1,3,4-oxadiazole-2(3H)-thione (5a) and 5-(4-amino-3-phenyl-2-thioxo-2,3-dihydrothiazol-5-yl)-1,3,4-oxadiazole-2(3H)-thione (5b) acted as the most active agents against Feline herpes virus, Feline corona virus, Herpes simplex virus-1 and Herpes simplex virus-2, whereas compound 2-(5-(2-phenylhydrazono)-4,5-dihydro-1,3,4-oxadiazol-2-yl)acetonitrile (11b) was the most effective against Vaccinia virus, Herpes simplex virus (TK-KOS-ACVr), Coxsackie virus B4 and Vesicular stomatitis virus.